Latent tuberculosis infection among contacts of patients with multidrug-resistant tuberculosis in New South Wales, Australia. Issue 3 (20th September 2021) - Chang, Vicky; Ling, Raphael Hongxi; Velen, Kavindhran; Fox, Greg J.
Background: Contacts of an individual with active tuberculosis (TB) disease have a higher risk of developing latent TB infection (LTBI) or active TB disease. Contact tracing is a public health measure that seeks to identify exposed contacts, screen them for co-prevalent TB and consider prophylactic treatment to prevent progression from LTBI to active TB disease. The investigators sought to determine the prevalence of LTBI and active TB disease among contacts of patients with multidrug-resistant (MDR)-TB in New South Wales, Australia. Methodology: A retrospective cohort study was performed among the contacts of patients diagnosed with MDR-TB between 2000 and 2016, inclusive, at seven chest clinics. Medical records were used to identify eligible contacts. Outcomes of screening and prophylactic treatment regimens offered to MDR-TB contacts with LTBI were characterised. Collected data included demographic information, screening tests results and initial management. Results: In total, 247 contacts of 55 MDR-TB patients were identified. LTBI was identified in 105 contacts (42.5%). Preventive treatment was received by 20 contacts with LTBI (32.3%) in the form of various regimens, ranging from one to three antimicrobials, with various doses and durations. One contact with LTBI who was untreated progressed to active TB disease during the study period, according to clinic notes. Conclusion: Contacts of MDR-TB patients have a high prevalence of LTBI. Management of these contacts varies substantially in New South Wales, reflecting a lack of definitive evidence for preventive therapy. Further research is required to determine the optimal management of this population. Given the high likelihood of multidrug resistance in strains responsible for LTBI among MDR-TB contacts, new research is needed to evaluate preventive therapies for this patient population https://bit.ly/2Tf4LLY